Thermo-erosional landforms in Siberian ice-rich permafrost - Morgenstern, Anne; Grosse, Guido; Arcos, David Rico; Günther, Frank; Overduin, Paul; Schirrmeister, Lutz (2013)
Of major concern in periglacial research is the question of how arctic permafrost landscapes react to climate change. Warming and thawing of ice-rich permafrost may result in substantial hydrological, geomorphological, ecological, and biogeochemical feedbacks which may have local to global impacts. While numerous studies have investigated thermokarst as one main process of permafrost degradation, data is sparse on thermal erosion, another widespread process of permafrost degradation. Siberian coastal lowlands underlain by ice-rich permafrost often feature streams, valleys, and valley networks that have formed under the influence of thermal erosion, but systematic regional studies have been lacking. We present an inventory of streams and valleys in three ice-rich lowland areas adjacent to the Laptev Sea using GIS-based analysis of remote sensing data, elevation models, and field investigations. The calculated total stream length is 4,153 km in the Cape Mamontov Klyk area, 1,541 km in the Lena River Delta area, and 2,047 km in the Buor Khaya Peninsula area; valley densities are 1.8, 0.9, and 1.0 km/km², respectively. Strong variations in the morphology and spatial distribution of streams and valleys are observed and can be attributed to differences in the size and relief characteristics of the study areas as well as to their predominant cryolithological properties, which are also influenced by previous degradation of the study areas by thermokarst. Based on the results, the evolution of different valley types in continuous ice-rich permafrost landscapes is discussed. The current valley pattern is largely the result of the late Holocene evolution of the hydrological system that is strongly connected to the degradation of ice-rich permafrost by thermal erosion.